Perbandingan Keberagaman Dewan Pengawas Syariah pada Bank Umum Syariah Indonesia dan Malaysia - Aulia Shofyani, Alvi; Alyaa, Azmatul; Aliyah Ainulhaq, Hamiyatul; Jamaluddin, Inayah Auliannisa; Hasna, Salsabila (Al-Musthofa: Journal of Sharia Economics, 2023)
Sharia Bank is a bank that has developed rapidly in Indonesia and Malaysia. Not only is the industry growing, but also development and diversity from the perspective of the Sharia Supervisory Board (DPS) in Islamic banks. This study aims to determine the diversity of the Sharia Supervisory Board of Islamic Commercial Banks in Indonesia and Malaysia. The method used in this research is qualitative. The data used is in the form of profiles of the Sharia Supervisory Board and sharia committees at official Sharia Commercial Banks (BUS) in Indonesia and Malaysia. The profile can be obtained from the official website of each BUS. The findings of this study indicate that the majority of BUS DPS in Indonesia and Malaysia are filled by men. Then from the last education side, the majority of DPA continued their studies in fields related to sharia. Most of them continue their studies in their home countries, but some choose to continue their studies abroad. Keywords: Sharia Supervisory Board, Sharia Committee, Indonesia, Malaysia